Synthesis of well-dispersed ZnO–Co–C composite hollow microspheres as advanced anode materials for lithium ion batteries. Issue 8 (16th January 2017) - Lu, Xiangjun; Xie, An; Jiang, Chunhai; Lu, Mi; Zhang, Yong; Zhong, Haichang; Zhuang, Shuxin
Abstract : Well-dispersed ZnO–Co–C composite hollow microspheres exhibit excellent electrochemical properties when used as anode materials for lithium ion batteries. Abstract : In this study, ZnO–Co–C composite hollow microspheres made up of massive nanometer-sized subunits are fabricated through a facile adsorption treatment at room temperature, followed by heating processing in inert atmosphere. When they function as active materials in lithium ion batteries, the as-obtained ZnO–Co–C composites show good electrochemical properties in terms of relatively high first coulombic efficiency, high specific capacity, distinguished cyclic property and exceptional rate capacity. ZnO–Co–C composite hollow microspheres possess an initial coulombic efficiency of about 70.1%, which is one of the best results for ZnO-based anodes reported. During repetitive lithiation–delithiation 300 times, a high discharge capacity of 794 mA h g −1 is harvested at 200 mA g −1 . The unique advantages, including metal Co and carbon modification, hierarchical hollow architecture and the nanoscale building blocks, account for the superiority in electrochemical performance of the ZnO–Co–C composites.